THE SERVICE SECTOR AS A DRIVER FOR IMPROVED LIVELIHOODS AND POVERTY ALLEVIATION. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the critical role of the service sector in promoting socio-economic development, particularly in the context of improving livelihoods and alleviating poverty. It highlights how the expansion of services contributes to employment generation, income growth, access to essential services, and inclusive development. Special attention is given to the role of services in empowering youth, women, and marginalized populations, as well as the importance of innovation and digital transformation. The article also outlines policy recommendations to enhance the sector’s impact and overcome existing challenges.